Comparative Study on the Characteristics and Performance of Ni-Impregnated and Non-Impregnated Natural Zeolite Catalysts in the Hydrocracking of Palm Oil to Biofuels - Istadi Istadi; Teguh Riyanto; Alda Salsabilla; Novaya Aulia Qotrunnada (Journal of Chemical Engineering Research Progress, 2025)
A catalyst was synthesized from Bayah’s natural zeolite with low crystallinity and uneven pore distribution. To overcome these limitations, the Bayah natural zeolite was subjected to activation and modification processes aimed at increasing its surface area, improving pore structure, and enhancing overall catalytic activity by impregnating with nickel metal which is active catalyst for cracking reaction. Therefore, this study compares the Ni-impregnated Bayah Natural Zeolite (Ni/ZAA) and non-impregnated Bayah Natural Zeolite (Ni/ZAA) with respect to performance of the hydrocracking of palm oil to biofuels (gasoline, kerosene, and diesel). The natural zeolite was pretreated via desilication using NaOH, followed by calcination. Ni was introduced into the zeolite through ultrasonic-assisted impregnation, and the resulting catalysts were characterized using XRD and XRF techniques. Hydrocracking was conducted at 500 °C with a WHSV of 0.1 min⁻¹ using both Ni/ZAA and non-impregnated ZAA catalysts. The liquid products were analyzed by GC-MS to determine selectivity and yield, including coke and gas formation. The desilication process enhanced slightly the Si/Al ratio and catalytic properties of the Bayah zeolite. While Ni impregnation was achieved, suboptimal processing conditions affected the quality of the resulting catalysts. Increasing Ni content improved crystallinity and catalytic activity but also promoted coke formation, which reduced reaction efficiency and liquid product yield. The highest biofuel yield was obtained using the non-impregnated ZAA catalyst, while the 10% Ni/ZAA catalyst showed reduced yield due to excessive coking and pore blockage. These findings suggest that while Ni enhances catalytic activity, excessive loading can lead to overactivity and reduced performance in biofuel production. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).